The Effect of High Environment Temperature on Physiological Condition and Productivity of Native Chicken - ., Gunawan; Sihombing, D T H (Indonesian Animal Sciences Society, 2004)
The optimal productivity of native chicken could be reached if reared on thermoneutral zone, a comfortable environment temperature. The comfortable environment temperature for the native chicken is still unknown, but it is predicted on around 18 to 25 Â°C. The native chicken placed on high temperature (25-31 Â°C) shows low productivity, including lower product and the weight of eggs, and also low growth rate. The decrease of egg number could reach 25% compared with those placed on comfortable environment temperature. The weight of 8 week-age ofnative chicken are also different i.e 257 g on high temperature, while on comfortable temperature could reach 427 g. This productivity decreased is mainly caused by the decreased of feed consumption, and also by the change of physiological condition of the chicken. The efforts to increase the native chicken production on high environment temperature are through selecting and crossing, manipulating environmental temperature, improving rearing management, and manipulating feedstuff and feed management. Manipulating feedstuff is the cheapest method, easy to do for increasing the amount of nutrient consumption. The method is by adding vitamine C, phosphor or giving sodium bycarbonate in the rations. The amount of vitamine C addition is 200-600 mg/kg ration on chicken producing eggs and 100-200 mg/kg ration to improve the chicken growth. Key words: High environment temperature, physiology, productivity, native chicken